O Manuscrito Perdido - Barahona, José (Portugal, 2010)
The film sets out in search of the manuscript and remakes the trip of Fradique Mendes in his flight, visiting some places that can shed light today on these same issues: the communities of the descendants of the African slaves, the indigenous villages where Cabral first arrived, and the camps of the landless. In the background social groups that have in common something more than 500 years: the struggle for freedom through the struggle for land tenure.
Verzio Film Festival Submission
Keywords: Documentary films